2017
DOI: 10.1016/j.ultsonch.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Congo red dye from aqueous solution with nickel-based metal-organic framework/graphene oxide composites prepared by ultrasonic wave-assisted ball milling

Abstract: Metal-organic frameworks (MOFs) were successfully synthesized by ultrasonic wave-assisted ball milling. In the absence of organic solvent, the coupling effect of ultrasonic wave and mechanical force played an significant role in the synthesis of MOFs. Adsorption of Congo red (CR) was studied in view of adsorption kinetic, isotherm and thermodynamics. The adsorbent was carried out using X-ray diffraction (XRD), thermogravimetric analysis (TGA), N adsorption-desorption isotherms, Raman spectroscopy and scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…The nitrogen adsorption‐desorption isotherms of Cu‐BTC are reported in Figure . As showed in Figure , the isotherms of Cu‐BTC are belong to Type‐I (b) isotherms . They rise sharply at low relative pressure and then reach to plateau, meaning the micro‐porous structure of the Cu‐BTC.…”
Section: Resultsmentioning
confidence: 91%
“…The nitrogen adsorption‐desorption isotherms of Cu‐BTC are reported in Figure . As showed in Figure , the isotherms of Cu‐BTC are belong to Type‐I (b) isotherms . They rise sharply at low relative pressure and then reach to plateau, meaning the micro‐porous structure of the Cu‐BTC.…”
Section: Resultsmentioning
confidence: 91%
“…The chart indicates that the adsorption on Ni‐MOFs@GO was endothermic. The structure of the composite is presented in Figure g, which indicated that the Ni‐MOFs are decorated well with GO; some wrinkles can be observed on the surface of GO according to its characteristics, along with the MOFs being embedded in the GO layers . As shown in Figure f, solvothermal‐synthesized MIL‐68 (Al) crystals grow on the nearly vertical planes of GO constructing a clear sandwich structure, which reflects that there is a chemical interaction between MIL‐68 (Al) and GO.…”
Section: Water Purificationmentioning
confidence: 88%
“…In addition, most of these pollutants are organic matter, and the introduction of these organic pollutants into environmental water is a serious issue that has attracted the attention of a large number of researchers . Fortunately, with excellent tunability and porosity, MOFs are considered to be a suitable adsorbent for these organic pollutants . Moreover, the concept of assembling MOFs and graphene‐based materials has been proposed and is believed to be able to hide the poor stability of MOFs and to create new pore space .…”
Section: Water Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of time: Ni-MOF (0.1 g) weighed in duplicate and transferred into 2 sample vials. Metal ion solution of 10 mL of working solution was added to each weighed sample and equilibrated by agitation for different time intervals of 1,5,15,25,45,65 and 85 min. The powered sample suspension was centrifuged for 5 min at 5000 rpm and decanted.…”
Section: Methodsmentioning
confidence: 99%